MORTALITY RISK DETERMINANTS IN ACUTE CORONARY SYNDROME: AN EVIDENCE-BASED LITERATURE REVIEW - ika ainur rofiah; Rudi Hariyono (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Acute Coronary Syndrome (ACS) remains a major global health problem and a leading cause of mortality, particularly in low- and middle-income countries where delays in treatment and limited access to reperfusion persist. Early identification of mortality determinants is essential for optimizing management and improving outcomes. This evidence-based review aimed to summarize contemporary predictors of mortality in ACS, incorporating clinical, demographic, laboratory, and hemodynamic factors. A comprehensive search was conducted using PubMed, Scopus, and Google Scholar for articles published between 2017 and 2025. Eleven studies met the eligibility criteria and were synthesized narratively. The findings show that hemodynamic instability, including hypotension, tachycardia, and cardiogenic shock, is the most consistent predictor of early and in-hospital mortality. Renal impairment, high Killip class, reduced left ventricular ejection fraction, and cardiac arrest at presentation also substantially increase risk. Age and comorbidities such as diabetes, hypertension, and chronic kidney disease contribute to both short- and long-term mortality. System delays, including prolonged symptom-to-door and door-to-balloon times, further worsen outcomes, particularly in resource-limited settings. The Simple Risk Index (SRI) emerges as a practical early risk-stratification tool. Strengthening early recognition, ensuring timely reperfusion, and improving management of comorbidities are crucial steps to reduce ACS-related mortality